Phytosociological study of Isla Patay Moro in Taklong Island National Marine Reserve, Nueva Valencia, Guimaras, Philippines. - Bela-ong, Andrea Lucyle (2017.)
small island may contain unique plant composition compared with larger islands due to size, isolation and explosure. Unfortunateley, information on small island in the tropic is limited considering that these islands are now subjected to impacts of climate change and increased anthropogenic pressure. In addition, these islands are also subjected to invasion of non-native species thay may alter the overall ecology of the island. There is lack of basic information on what constitute a tyupical flora of small islands. Thus, phytosociological study was conducted in Isla Patay moro, one of the many small islands withion Taklong Island National marine Reserve, Nueva Valencia, Guimaras, Philippines from December 2016-toApril 2017 in an attempt to provide relevant information. Specifically it described, identified and classified the flora present in the islands as well as described the community structure in terms of species composition, stand hight, stand basal area, importance value and species diversity and eveness. The flora of the island is dominated by trees and shrubs and few vines. A total of 30 species were identified representing 19 families. The most common and dominant species was Streblus asper with an importance value of 57.80. The total sampled area of the islands was 600 m2 and the totalstand basal cover of 20,450.17 m2/ha. The species diversity of the islands was 1.17 and 0.87 by Shannon and Simpson diversity indices, respectively, implying low species diversity. The stand height of the flora ranged from 2.2 to 8.47 meters. Presence of exotic species, Lantana camara, Leucaena leucocphla were also found. This study may serve as a baseline for further researchesand the results may aid in the development of floristic conservation activities particularly for the presence of invasive of non-native species that may alter the natural flora in the future leading to ecological instability of the island. This is the first systematic surveu of higher vascular plants on the island.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Island Flora -- Taklong Island, Guimaras; Phytosiological study -- Isla Patay, Taklong Island, Guimaras